Korupsi sebagai Jarīmah Amanah: Rekonstruksi Hukum Pidana Islam dalam Tafsir al-Qurṭubī - Anas Kholik; Kholilurrohman Kholilurrohman (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Corruption remains a serious problem in state governance despite continuous strengthening of criminal regulations and oversight mechanisms. This condition indicates that a legal–formal approach has not fully captured the nature of corruption as a public crime with extensive social consequences. In modern legal discourse, corruption is commonly understood as an administrative and economic offense, while its dimensions as a betrayal of public trust and a source of structural damage tend to be marginalized. In contrast, the Qur’an conceptualizes such acts as violations of public amanah and as forms of fasād that disrupt social justice. This article aims to reconstruct the concept of criminal law on corruption through the perspective of tafsīr aḥkām, with Tafsīr al-Qurṭubī as the primary reference. This study employs a thematic exegesis approach (tafsīr mawḍū‘ī) by examining Qur’anic verses related to trust (amānah), wealth, abuse of authority, and social corruption, which are analyzed within the frameworks of fiqh jināyah and maqāṣid al-sharī‘ah. The findings indicate that, according to al-Qurṭubī, corruption cannot be reduced to a purely financial offense but should be understood as a jarīmah al-amānah that potentially generates structural fasād. Corruption is classified within the domain of ta‘zīr crimes, with the severity of punishment determined by the extent of social harm it produces. In certain circumstances, it may be conceptually characterized as a form of severe fasād bearing similarities to the nature of ḥirābah. These findings affirm an epistemological foundation for developing a more integrative paradigm of anti-corruption criminal law, oriented toward the protection of public trust and the realization of public welfare.